Analysis of Content Words in the Song â€œWho Saysâ€ by Selena Gomez - Arrisma Delimasari; Nisrina Fauziah; Dhania Puspita Anjarsari; Paulina Besty Fortinasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
To ensure that students can understand the meaning of the English they are learning, knowledge of content and function words are two important aspects that must be possessed. The aim is to avoid misunderstanding in the interpretation process, both in written and oral texts. Nevertheless, this research was made with the aim of knowing types of content words appeared in the lyrics of Selena Gomez's song "Who Says" and the function of the dominant content word in this song. In order to obtain the required data, researchers used a qualitative descriptive method. Meanwhile, the lyrics of the song were analyzed manually by giving the symbols "V", "N", "Adj", and "Adv" according to the word class. With the result that the data could be obtained, they were 83 words of nouns, 74 words of verbs, 32 words of adjectives, and 3 words of adverbs. In addition, of the 83 nouns, there was the word "you're" which was the dominant or most appearing word that could function as a subject as well as an object.